Sequential one-stage combined procedure for treating bilateral developmental hip dysplasia after walking age. Issue 7 (July 2019) - Li, Haibing; Ye, Wensong; Xu, Lujie; Li, Li; Zhu, Weiwei; Zheng, Zefeng
Objective: This study aimed to evaluate outcomes of the sequential one-stage combined procedure for treating bilateral developmental dysplasia of the hip (DDH) that was diagnosed after walking age. Methods: Thirty-five patients (70 hips) with late-presenting bilateral DDH were treated with the sequential one-stage combined procedure. Hips were reclassified according to the operative time and divided into the first and the second operated hips. The outcomes were compared clinically and radiographically between the two sides preoperatively and postoperatively. Results: The mean interval time between the two procedures was 5.9 months (range: 2–9 months). The first operated hip achieved better results than did the second operated hip. A total of 68.6% (24/35) of the patients in our series had an asymmetric outcome. Conclusions: The sequential one-stage combined procedure is a challenge, but a reasonable alternative surgery for bilateral DDH in children after walking age. An asymmetric outcome is a special complication of this procedure.